The Correlation between Students Perception about Anatomy Laboratory Peer Mentoring andThe Achievement of Learning Objective of Medical Students in UNS - Firdausul Ma'rifah; Ari Natalia Probandari; Sumardiyono . (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Peer mentoring activity has been applied in medical education system in common university include in UNS. Peer teaching and learning is given to the students so that they understand the material before attend the anatomy laboratory activity. But there is a policy from educational medical faculty of UNS that peer mentoring will be deleted. Methods: This research was an analytic observational research with cross sectional design,and held in Medical Faculty,UNS,in November 2014.The participants were 200 second year UNS medical student.This research was using perception assistance anatomy laboratory questionnaire instrument that had been validated.Data analyzedusing Spearman Rank Correlation. Results: The result of statistic test indicated correlation between peer mentoring perception thoroughly and studying goal achievement was not significant or meaningful. (p = 0,06 and r = 0,133). Conclusion: Students perception about anatomy laboratory peer mentoring is not increase achievement of learning objective of medical students in UNS. Keywords: perception of peer mentoring, learning objective, Anatomy Laboratory.